Some Causes are More Equal than Others? Behavioral Spillovers in Charitable Giving - Claes Ek (Lund University, School of Economics and Management, Department of Economics, 2015)
People can often contribute to prosocial causes by several means; for instance, environmentally friendly activities include sorting household waste, buying organic products, and donating to NGOs. Policy to encourage prosocial behavior is sometimes directed only towards a particular activity, however, and such policies may give rise to `behavioral spillovers', affecting efforts on other prosocial activities. We examine such spillovers in the lab. In a version of the dictator game, experimental subjects could donate to two different real-world charities, and to simulate activity-specific policy, the relative productivity of the charities varied. We hypothesize, first, that an increase in the productivity of one charity will `crowd out' contributions to the other charity. Second, we introduce several treatments to test whether crowding occurs even across (possibly very) dissimilar alternatives. Crowding-out occurs significantly in all cases, but the effect is systematically weaker, the more dissimilar are the charity alternatives. In our most dissimilar treatment, it is only half as large as when alternatives are very similar.
Keywords: C91; D03; H41; 330; charitable giving; dictator game; public goods; prosocial behavior